Implementasi Keamanan Data Keuangan di SMK Swasta Musda Perbaungan Menggunakan Metode RC4 - Rista; Arjon Samuel Sitio (Sisfokomtek, 2020)
Data security and confidentiality is currently a very important issue and continues to grow. Several cases concerning data security are currently a job that requires handling and security costs that are so large. To maintain the security and confidentiality of messages, data, or information so that no one can read or understand it, except for the rightful recipients, a data security system application with an encryption method using the rc4 algorithm is designed. RC4 (Rivest Cipher 4) is a synchrone streamcipher, which is a cipher that has a symmetric key and encrypts the plaintext digit by digit or byte per byte by combining binary operations (usually XOR) with a semi-random number.